Eksotika Fotografi Makanan Pada Masakan Tradisional Sumatera Barat - Farzy, Agus Setyawan (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2022)
Indonesian traditional cuisine itself has begun to be forgotten by today's generations due to globalization's emergence of various foreign cuisines. Many factors make some traditional dishes become unknown or in demand. This case is because, due to the lack of introduction to traditional cuisine itself, it causes people not to know about the existence of some traditional dishes. Preserving the nation's traditional cuisine is the responsibility of the Indonesian people. West Sumatran traditional cuisine is one of Indonesia's traditional dishes with various dishes with distinctive culinary tastes, namely: spicy, sweet, sour, and savoury, all of which can spoil the tongue of those who eat it. Traditional West Sumatran cuisine can be found in traditional markets in West Sumatra. However, not all traditional West Sumatran cuisine types are available in traditional markets; traditional dishes are made only on certain days, such as Eid al-Fitr, Eid al-Adha, traditional ceremonies, and weddings ceremonies. On that basis, this research aims to explore West Sumatra's traditional cuisine with photography techniques more deeply. In this study, the authors describe traditional foods displayed and combined with photographic techniques. The research results show that, through photography techniques, the exotica of traditional West Sumatran cuisine can be explored. This research also found that, in order to maximize food exploration through photographic techniques, photographers need to work closely with food stylists.